E-learning Capacity Building for Kabale University Teaching Staff - Kabale University (Kabale University, 2022)
The training workshop explored the use of the Learning Management System (LMS) in teaching and learning. The participants went through an Orientation to eLearning course to familiarize them with the online learning environment. It also focused on application of instructional theory and design for online learning in content development. In addition, it also explored the approaches to online teaching and how to respond to the technical support needs for eLearning in various contexts. At the end of each training, participants engaged in a discussion to build a consolidated approach to eLearning for capacity development for the University. The way forward and strategy of the workshop was shared as presented in the next sections